2022
DOI: 10.1101/2022.11.04.22281959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wearable-Derived Maternal Heart Rate Variability As A Novel Digital Biomarker of Preterm Birth

Abstract: Despite considerable health consequences from preterm births, their incidence remains unchanged over recent decades, due partially to limited screening methods and limited use of extant methods. Wearable technology offers a novel, noninvasive, and acceptable way to track vital signs, such as maternal heart rate variability (mHRV). Previous research observed that mHRV declines throughout the first 33 weeks of gestation in term, singleton pregnancies, after which it improves. The aim of this study was to explore… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, in our study, RMSSD showed the least influence in estimating PTB. Furthermore, Jasinski et al 62 explored maternal HRV trends and their association with gestational age and time until birth. While this study showed a strong fit for weeks until birth in predicting maternal HRV changes in both term and preterm pregnancies, our study extends this understanding by discovering distinct patterns in PTB abnormality scores…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in our study, RMSSD showed the least influence in estimating PTB. Furthermore, Jasinski et al 62 explored maternal HRV trends and their association with gestational age and time until birth. While this study showed a strong fit for weeks until birth in predicting maternal HRV changes in both term and preterm pregnancies, our study extends this understanding by discovering distinct patterns in PTB abnormality scores…”
Section: Discussionmentioning
confidence: 99%
“…Assessed continuously using the Oura ring 61 during the second and third pregnancy trimesters, the result of this study supports the potential of tracking HRV for PTB detection. Additionally, Jasinski et al 62 have explored the relationship between maternal HRV and gestational weeks and time until birth, enrolling 241 pregnant women wearing WHOOP straps 63 . While these approaches highlight the significance of maternal HRV monitoring, they have not investigated the potential of PTB estimation during pregnancy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, low RMSSD in placental abruption as compared to healthy individuals showed HRV's potential for prediction application. Placental abruption is a significant contributing factor to preterm birth, a condition associated with sympathetic predominance of the ANS in the existing literature (Aye et al, 2018;Jasinski et al, 2022). Placental abruption involves the partial or complete separation of the placenta from the uterine wall before the onset of labor.…”
Section: Discussionmentioning
confidence: 99%
“…With the ubiquity of the smartphone [15], and the increasing popularity of wearable smart devices [16] such as the smartwatch and the smart ring, the use of such tools for monitoring pregnancy-related signs and symptoms and greatly transforming current knowledge of this important metamorphosis is a potential reality. While the body of research involving personal DHTs in pregnancy is small, a number of small preliminary studies have shown potential utility in using wearables for tracking activity, sleep, and physiologic metrics such as HR and HRV as predictors of pregnancy-related outcomes such as preterm birth and delivery readiness [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%